R-dl-verapamil downmodulates multidrug resistance of KBv200 cells to vincristine and doxorubicin - Fang Gang; Yang Yu-long; Li Jie-shou; Zhang Zu-xuan (Acta Pharmacologica Sinica; Vol 20, No 7 (July 1999): Acta Pharmacologica Sinica, 2016)
AIM: To study the attenuation of multidrug resistance (MDR) by R-dl-verapamil (R-Ver) and the acute animal toxicity of R-Ver, and to compare these results of R-Ver with the results of dl-verapamil (Ver). METHODS: Cytotoxicity was determined by tetrazolium (MTT) assay. Cellular accumulation of doxorubicin (Dox) was measured by fluorescence spectrophotometry. Acute animal toxicity was tested by i.p. drug administration in BALB/c mice. RESULTS: R-Ver attenuated MDR of KBv200 cells to vincristine (VCR) and Dox. This attenuation ability was dose-related, and was also dependent on drug exposure time. R-Ver 1.25 mumol.L-1 increased the sensitivity of KBv200 cells to VCR (P < 0.01) with a 24-h period of drug exposure. R-Ver downmodulated MDR and increased cellular Dox accumulation of KBv200 cells as effectively as Ver, but possessed lower acute toxicity in BALB/c mice. While LD50 of Ver was 60 (49-73) mg.kg-1, LD50 of R-Ver was 166 (137-202) mg.kg-1. CONCLUSION: R-Ver downmodulated the MDR to VCR and Dox at 1.25 mumol.L-1, and this effect on VCR can be realized with drug exposure duration of 24 h.